Theology from the beginning : essays on the primeval history and its canonical context - Schüle, Andreas (Forschungen zum Alten Testament, 2017)
The Primeval History (Genesis 1-11) is one of the most complex theological compositions of the Old Testament/the Hebrew Bible. Woven into its multi-layered text one finds reflections on an array of fundamental questions: How did the world come into being? Who is its creator? What role does humankind play in the larger scheme of creation? Why is the world that God made not a perfect one? And finally, is it possible to lead a meaningful and even happy life despite the unpredictabilities of existence? The essays by Andreas Schule assembled in this volume address these and related questions through close readings of Genesis 1-11 and by relating them to kindred textual traditions throughout the Old Testament/the Hebrew Bible.